2006
DOI: 10.1037/0022-006x.74.3.482
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of treatment for children with sexual behavior problems: Ten-year follow-up.

Abstract: This study prospectively follows 135 children 5-12 years of age with sexual behavior problems from a randomized trial comparing a 12-session group cognitive-behavioral therapy (CBT) with group play therapy and follows 156 general clinic children with nonsexual behavior problems. Ten-year follow-up data on future juvenile and adult arrests and child welfare perpetration reports were collected. The CBT group had significantly fewer future sex offenses than the play therapy group (2% vs. 10%) and did not differ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 22 publications
1
104
0
4
Order By: Relevance
“…That is, for which children will early CSBP be a transient developmental phenomenon, and for which will early SBP be an indicator of persistent maladjustment? It is clear that the majority of children with SBP do not continue to demonstrate problematic sexual behaviors, including sexual offending, into adolescence and adulthood (Carpentier et al, 2006;Letourneau et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, for which children will early CSBP be a transient developmental phenomenon, and for which will early SBP be an indicator of persistent maladjustment? It is clear that the majority of children with SBP do not continue to demonstrate problematic sexual behaviors, including sexual offending, into adolescence and adulthood (Carpentier et al, 2006;Letourneau et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In general, boys are more likely to be referred for intervention for SBP than are girls (Bonner et al, 1999;Carpentier et al, 2006;Gray et al, 1999;Ray & English, 1995). One notable exception, however, is Silovsky and Niec's (2002) sample of preschool children in which 65% of the children referred for treatment were girls.…”
Section: Gendermentioning
confidence: 99%
“…Good results have also been reported across a number of short-term interventions with juvenile offenders younger than age 12 (Chaffin et al, 2008). Researchers found that one brief treatment for preteens reduced the risk of future sex offenses to levels comparable with those of children who had no history of inappropriate sexual behavior (Carpen tier, Silovsky, and Chaffin, 2006).…”
Section: Discussionmentioning
confidence: 74%
“…Entre autres, on y propose la Formation interactive parent-enfant comme piste complémentaire visant l'amélioration des interventions auprès (Bonner, Walker et Berliner, 1999;Gagnon, 2003;Pithers, et collab., 1998b;Staiger, 2005;Silovsky, et collab., 2007) ou en présentant les résultats d'un suivi longitudinal d'un groupe d'enfants ayant reçu un traitement cognitif-comportemental (Carpentier, Silovsky et Chaffin, 2006). Ces auteures en sont venues à la conclusion que l'efficacité de l'approche cognitive-comportementale semble supérieure à celles d'autres formes de traitement.…”
Section: Interventions Auprès Des Enfants Manifestant Des Comportemenunclassified